Standardised measurement of physical capacity in young and middle-aged active adults with hip-related pain: recommendations from the first International Hip-related Pain Research Network (IHiPRN) meeting, Zurich, 2018. Issue 12 (19th December 2019) - Mosler, Andrea Britt; Kemp, Joanne; King, Matthew; Lawrenson, Peter R; Semciw, Adam; Freke, Matthew; Jones, Denise M; Casartelli, Nicola C; Wörner, Tobias; Ishøi, Lasse; Ageberg, Eva; Diamond, Laura E; et al.
Abstract : Hip-related pain can significantly impact quality of life, function, work capacity, physical activity and family life. Standardised measurement methods of physical capacity of relevance to young and middle-aged active adults with hip-related pain are currently not established. The aim of this consensus paper was to provide recommendations for clinical practice and research on standardised measurement methods of physical capacity in young and middle-aged active adults with hip-related pain. Four areas of importance were identified: (1) clinical measures (range of motion, muscle strength, functional impairments), (2) laboratory-based measures (biomechanics and muscle function (muscle activity, size and adiposity)), (3) physical activity, and (4) return to sport/performance. The literature was reviewed, and a summary circulated to the working group to inform discussion at the consensus meeting. The working group developed clinical and research recommendations from the literature review, which were further discussed and modified within the working group at the consensus meeting. These recommendations were then presented to all 38 International Hip-related Pain Research Network (IHiPRN) participants for further discussion, refinement and consensus voting. Therefore, the recommendations voted on were based on a combination of current evidence and expert opinion. The consensus meeting voted on 13 recommendations, six of which were clinically orientated, and seven more research specific. We recommended that clinicians working with young and middle-aged active adults with hip-related pain assess strength using objective methods of measurement, and clinically assess performance of functional tasks, including walking and running. Physical activity should be quantified using both self-reported and objective measures, and patient expectations of recovery should be quantified prior to treatment. It was recommended that return to physical activity (including sport and occupation) be quantified, and sport-specific activities should be assessed prior to return to sport. The IHiPRN participants were uncertain regarding recommendations for range of motion assessment. Research recommendations were that the measurement properties of range of motion, strength and functional performance tests be investigated, reported and improved in both clinical and research settings. Reporting of movement-related parameters (biomechanics and muscle function) should be standardised and the relationship among movement-related parameters, symptoms, function, quality of life, and intra-articular and imaging findings should be investigated. Quantification of return to physical activity (including sport and occupational demands) is required in future research, and the return to sport continuum should be used. Future research is required to determine the best criteria for rehabilitation progression and return to physical activity following hip-related pain management.